Preparation of A Measurement to the Affirmative Behavior for the Students at the University of Baghdad - أحلام حسين ورة أ.د.غسان حسين سالم (College of Education for Women, 2019)
Self-Assertion is the individual ability to express any emotion well, except the anxiety. The decrease of the individuals asserting behavior makes them face many difficulties that prevent their social adjustment. Moreover it reflexes many negative behavioral and physical cases. The individual, who fails to express his or her negative feelings in required situations, feels with dissatisfaction, loneliness, depression, anxiety, social anxiety, conflict, and psychological disorder. Accordingly, the importance of this study is represented in studying the self-assertion and studying the university students who reflect the strength of society. The following are the two aims of the study: 1. Construct an asserting behavior scale. 2. Measuring the asserting behavior of the university of Baghdad students. In order to verify the aims of the study, the researchers construct an asserting behavior scale. The sample is represented by (400) students of University of Baghdad for both humanities and scientific colleges. The researchers use the statistical tools to find out the validity and reliability and then the scale is applied on (476) students. The results of the study show that: 1. A scale of asserting behavior has been constructed. 2. The university students have the asserting behavior.